Graphene-Based Flexible Sensors for Simultaneous Detection of Ascorbic Acid, Dopamine, and Uric Acid - Meng, Shuaishuai; Liu, Yaming; Wang, Li; Ji, Xixi; Chen, Yun; Zheng, Tingting; Yu, Jie; Feng, Huanhuan (Frontiers in Bioengineering and Biotechnology, 2021)
Many diseases are closely related to abnormal concentrations of ascorbic acid (AA), dopamine (DA), and uric acid (UA). Therefore, the detection of these small molecules is significant for monitoring life metabolism and healthy states. Electrochemical detection has been widely used to detect small molecules due to its good selectivity, high sensitivity, and good economics. Fabrication and application are two sides of the coin, and we cannot give up one for the other. Graphene (GN) is a very suitable material for electrochemical sensing due to its excellent catalytic performance and large specific surface area. It possesses many excellent properties but cannot hold itself alone due to its nanoscale thickness. Herein, we have fabricated three-dimensional (3D) GN nanosheets (GNSs) on flexible carbon cloth (CC) by thermal chemical vapor deposition (CVD). The GNSs/CC can successfully detect AA, DA, and UA simultaneously. We find that these GNSs/CC sensors show good performance with 7 h CVD modification. The linear ranges of AA, DA, and UA are 0.02–0.1, 0.0005–0.02, and 0.0005–0.02 mM, respectively. The detection sensitivity rates of AA, DA, and UA are 5,470, 60,500, and 64,000 μA mM−1 cm−2, respectively. Our GNSs/CC flexible sensors can be successfully applied in the human serum for UA detection. The result matches with commercial sensors very well.